Desain Rancangan Pembangkit Tenaga Surya di Gedung Pendidikan Teknik Bangunan - Farid Wajdy Sitorus; Haikal Budi Utomo; Egy Wira Indana; Eka Dodi Suryanto; Dian Putra Saragi (JOURNAL SAINS STUDENT RESEARCH, 2026)
The rooftop of the University of Medan Construction building which has an area of 210 m2 can be used as a solar power plant (PLTS). Installing PLTS in buildings has several advantages, namely as a long-term energy investment and easy to integrate with the grid electrical system. PLTS is designed to save electricity consumption. In addition, if PLTS is connected to a battery, it can meet some of the energy needs at night. To design a PLTS installation in the Integrated Laboratory building, this research uses technical and economic analysis methods. Technical analysis is carried out to determine the capacity and number of PV mini-grid components required for installation. While the economic analysis aims to calculate the investment costs and the length of time for the return on investment compared to buildings without PV mini-grid installations. Based on this research, the results show that the amount of energy required for the Integrated Laboratory building is 482.148 kWh, while the planned PLTS is able to provide energy of 216,128 kWh. The PLTS design requires an initial investment of Rp. 927,700,894,-. So by using the Payback Period (PP) method, it can be concluded that the planned design is feasible, because the comparison of the cost of return on investment is 9.13 years faster than the project age that has been determined previously, which is 20 years.